Quantum Confinement in Cadmium Selenide Multilayer Thin Films Using Physical Vapour Deposition Method - M. Melvin David Kumar; Suganthi Devadason; S. Rajesh (Журнал нано- та електронної фізики)
Nanocrystals of CdSe have been produced in SiOx matrix layer and in ZnSe heterostructure layer by thermal evaporation method. Structural studies were done by X-ray diffractometer. Quantum confinement effect of CdSe nanocrystals was analyzed from optical studies. Bulk CdSe has band-gap energy of 1.756 eV that can be shifted to larger values by reducing the crystal size to dimensions smaller than the Bohr radius of the exciton. Experimentally measured band-gap shifts with respect to the bulk value for quantum dot thin films are compared with the predictions of the effective mass approximation model (i.e., Brus model) and Quantum mechanical model. Sizes of the crystallites calculated from both models were coincident with each other.